FRI0089 Assessing maintenance of remission with reduced dose etanercept plus methotrexate, methotrexate alone, or placebo in patients with early rheumatoid arthritis who achieved remission with etanercept and methotrextate: the prize study. (23rd January 2014) - Emery, P.; Hammoudeh, M.; FitzGerald, O.; Combe, B.; Martin Mola, E.; Bukowski, J.; Pedersen, R.; Williams, T.; Gaylord, S.; Vlahos, B.
Abstract : Background: During Phase 1 of the 52 wk open-label PRIZE study treatment of patients (pts) with early (mean 6 mos.) moderate-severe rheumatoid arthritis (RA), who were methotrexate (MTX)/biologic naïve, with 50 mg etanercept (ETN) + 10-25 mg MTX yielded a 70% remission rate with no significant radiographic progression. 1 Pts achieving remission in Phase I were randomized to a double-blind 39-wk period of reduced (25mg) ETN + MTX or withdrawn (MTX alone or placebo, PBO) therapy (PRIZE Phase 2). Objectives: To assess sustained remission (DAS28 and ACR/EULAR Boolean [AEB]), other clinical, radiographic, and safety outcomes in pts subsequently treated with reduced dose ETN or PBO after remission induction during PRIZE Phase 1. Methods: Pts achieving DAS28 remission by wk 52 (≤3.2 at wk 39, <2.6 at wk 52) in Phase 1 (n=193) were randomized 1:1:1 to ETN25/MTX: MTX + PBO injection: PBO capsules + PBO injection at wk 52. Pts with DAS28>3.2 (> low disease activity, LDA) received corticosteroid boosts at wks 56 or 64; pts not achieving LDA at the next visit withdrew. Remission and other standard clinical outcomes were assessed. Odds ratios and significance were determined by logistic regression models. Results: ETN/MTX resulted in a significantly higher proportion of pts in sustained and AEB remission than MTX alone or PBO. More ETN/MTX treated pts achieved DAS28 LDA than PBO. Over Phase 2 radiographic progression (mTSS >0.5) occurred in <12% of pts, with no significant difference between treatment arms; at Phase 1 baseline the mTSS scores were 8.06, 8.46 and 7.59 for ETN25/MTX, MTX and PBO, with changes of 0.44, -0.5 and 1.41 by last observations in Phase 2 (LOCF), indicating no clinically relevant radiographic progression in any of these treatment groups ETN/MTX treatment resulted in more pts achieving ACR50 and 70 than PBO. There were no unexpected safety findings. Conclusions: Of the moderate-severe early RA pts achieving DAS28 remission during a 52 wk induction (50 mg ETN/MTX in PRIZE Phase 1), 63.5% maintained remission (DAS28<2.6 at wk 76 & 91 visits) with ETN25/MTX, 38.5% with MTX and 23% with PBO over 39 subsequent wks. There was no significant radiographic progression in any treatment group. There were no unexpected safety findings. References: Emery P et al. American College of Rheumatology/ARHP Annual Scientific Meeting – 2012;64(10):S160; Abstract 368. Acknowledgements: The PRIZE study was funded by Pfizer Inc. Disclosure of Interest: P. Emery Consultant for: Abbott, Bristol-Myers Squibb, Merck, Novartis, Pfizer Inc, Roche-Chugai, UCB Pharma Ltd, M. Hammoudeh Consultant for: Pfizer Inc, Roche, Abbott Laboratories, O. FitzGerald Consultant for: Bristol-Myers Squibb, Roche, Abbott Laboratories, Pfizer Inc, UCB Pharma Ltd, B. Combe Consultant for: Bristol-Myers Squibb, Merck, Pfizer Inc, Roche-Chugai, UCB Pharma Ltd, E. Martin Mola Consultant for: Pfizer Inc, Roche, Celgene Ltd, UCB Pharma Ltd, Speakers bureau: Pfizer Inc, Roche, UCB Pharma Ltd, J. Bukowski Employee of: Pfizer Inc, R. Pedersen Employee of: Pfizer Inc, T. Williams Employee of: Pfizer Inc, S. Gaylord Employee of: Pfizer Inc, B. Vlahos: None Declared